Concepts of person and Christian ethics - Rudman, Stanley (New studies in Christian ethics, 1997)
The concept and definition of personhood is central to current debates over ethics. Should 'personhood', for example, determine the allocation of scarce medical resources, and its perceived absence allow the termination of life? In a wide-ranging discussion notable for its clarity, Stanley Rudman's 1997 book traces the development of modern ideas about personhood. He argues that concepts of person are socially constructed, and that the relational understanding of persons in a number of theological discussions can act as an important corrective to the individualistic notions of person which have been popular in secular philosophy since the Enlightenment. Early Christian views of divine speech, communication and relations between the Trinity can help to define an ethic which understands personhood in relation to other people, to the environment, and to God.